Respuesta :
Answer:
$96
Step-by-step explanation:
Micheal's money = x
John's money = y
Ian's money = z
x + 18 = y
2/3x - 2 = z
x + y + z = $272
rearrange the equations we have:
2/3x = z + 2
x = 3/2(z + 2)
x = y - 18
Substitute y - 18 into x values:
3/2(z + 2) = y - 18
y - 18 + y + z = 272 --> 2y - 18 + z = 272
Solve for y:
Firstly rearrange
2y - 18 + z = 272 --> z = 272 + 18 - 2y, which simplifies to z = 290 - 2y
substitute into the formula:
3/2((290 - 2y) + 2) = y - 18
3/2(292 - 2y) = y - 18
438 - 3y = y - 18
4y = 456
y = $114
Substitute back into the formula to find z:
z = 290 - 2(114)
z = 290 - 228
z = $62
Put all of this back into one of the original formulas to find x:
x + y + z = 272
x + 114 + 62 = 272
x + 176 = 272
x = $96
Let,
- Michael has = x dollars
- John has = 18+x
- Ian has = 2-2/3x
Total amount = $272
Now, ATQ
[tex] \tt \nrightarrow \: x + 18 + x + 2 - \frac{2}{3} x = 272[/tex]
[tex] \tt \nrightarrow \: 2x + 20- \frac{2}{3} x = 272[/tex]
[tex] \tt \nrightarrow \: 6x + 60 - 2x = 816[/tex]
[tex] \tt \nrightarrow \: 4x + 60 = 816[/tex]
[tex] \tt \nrightarrow \: 4x = 816 - 60[/tex]
[tex] \tt \nrightarrow \: 4x = 756[/tex]
[tex] \tt \nrightarrow \: x = 189[/tex]
➪ Thus, Michael has $189...~